On the Role of Pacific‐Atlantic SST Contrast and Associated Caribbean Sea Convection in August–October U.S. Regional Rainfall Variability. Issue 11 (5th June 2020) - Kim, Dongmin; Lee, Sang‐Ki; Lopez, Hosmay; Foltz, Gregory R.; Misra, Vasubandhu; Kumar, Arun
Abstract: This study investigates the large‐scale atmospheric processes that lead to U.S. precipitation variability in late summer to midfall (August–October; ASO) and shows that the well‐recognized relationship between North Atlantic Subtropical High and U.S. precipitation in peak summer (June–August) significantly weakens in ASO. The working hypothesis derived from our analysis is that in ASO convective activity in the Caribbean Sea, modulated by the tropical Pacific‐Atlantic sea surface temperature (SST) anomaly contrast, directly influences the North American Low‐Level Jet and thus U.S. precipitation east of the Rockies, through a Gill‐type response. This hypothesis derived from observations is strongly supported by a long‐term climate model simulation and by a linear baroclinic atmospheric model with prescribed diabatic forcings in the Caribbean Sea. This study integrates key findings from previous studies and advances a consistent physical rationale that links the Pacific‐Atlantic SST anomaly contrast, Caribbean Sea convective activity, and U.S. rainfall in ASO. Plain Language Summary: This study investigates the large‐scale atmospheric processes that modulate U.S. rainfall variability in late summer to midfall (August–October; ASO). We show that the well‐recognized relationship between the Bermuda High and U.S. rainfall in peak summer (June–August) is not applicable in ASO. Instead, both observations and model simulations show that in ASO atmospheric convective activity in the Caribbean Sea, modulated by the Pacific‐Atlantic interbasin sea surface temperature (SST) anomaly contrast, directly influences the atmospheric low‐level jet that carries warm and moist air from the Gulf of Mexico into the United States and thus affects U.S. rainfall variability. This study integrates key findings from previous studies and advances a consistent physical rationale that links the Pacific‐Atlantic SST anomaly contrast, Caribbean Sea convective activity, and U.S. rainfall in ASO. Key Points: This study investigates the large‐scale atmospheric conditions that modulate U.S. rainfall variability in August–October The well‐recognized relationship between NASH and U.S. rainfall in peak summer is not applicable in August–October Earlier key findings are integrated to link the Pacific‐Atlantic SST contrast, Caribbean Sea convection, and U.S. rainfall in ASO